Applications of Metal Nanoparticles in Healthcare and Food Safety - Chen, Sihua (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The increased world population has led to a rise in pollution, raising the risk of food contamination and foodborne illness. It is often said that illness enters by the mouth. Food spoilage has always been a great hazard to human health. Therefore, ensuring the safety of food is essential in the pursuit of good health. The advent of nanotechnology has sparked potential in the food industry. Nanotechnology has also shown its ability to reduce cases of foodborne diseases, thereby improving global food security from the root. With the introduction of nanoparticles (NPs), particularly metal NPs like gold and silver, food processing and delivery methods have been further refined. These NPs have demonstrated effective resistance against pathogens. Their antimicrobial abilities play a vital role in nano materials for food packaging. The main mechanism of metal NPs involves their interaction with bacterial cell walls, which enhances cell wall permeability and achieves cell wall damage. At the same time, toxic radicals are released from the NPs and can be dissolved to be absorbed by bacteria. These results in the leakage of cellular contents, inhibiting cell replication, and ultimately, cell death. The application of metal-based NPs significantly contributes to food safety. Therefore, in this work, the applications of various nanomaterials in food safety and healthcare are discussed in detail. This work will contribute to promoting the deep application of nanomaterials in food safety and healthcare.